2011
DOI: 10.1038/ni.1995
|View full text |Cite
|
Sign up to set email alerts
|

Opposing regulation of the locus encoding IL-17 through direct, reciprocal actions of STAT3 and STAT5

Abstract: Summary IL-2, a cytokine linked to human autoimmune diseases, limits IL-17 production. We show that deletion of STAT3 in T cells abrogates IL-17 production and attenuates autoimmunity associated with IL-2 deficiency. While STAT3 induces IL-17 and RORγt and inhibits FOXP3, IL-2 inhibited IL-17 independently of FOXP3 and RORγt. We found that STAT3 and STAT5 bound to multiple common sites across the Il17 genetic locus. The induction of STAT5 binding by IL-2 was associated with a reduction in STAT3 binding at thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
534
2
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 524 publications
(567 citation statements)
references
References 50 publications
26
534
2
5
Order By: Relevance
“…65 The binding ratio of different STAT members to the same STAT sites can affect gene expression and cell differentiation dramatically. [66][67][68] In our study, we found IL-15 stimulation dramatically activated STAT5 signaling and induced more pSTAT5 binding to the nine STAT sites on the promoter of ATM, 53BP1, MDC1 DNA damage genes. As a consequence of this binding, there are less pSTAT3, more transcriptionally repressive histones (H3K27) and less transcriptionally active histones (H3K4, P300, Acy 300) binding to the promoters.…”
Section: Discussionmentioning
confidence: 81%
“…65 The binding ratio of different STAT members to the same STAT sites can affect gene expression and cell differentiation dramatically. [66][67][68] In our study, we found IL-15 stimulation dramatically activated STAT5 signaling and induced more pSTAT5 binding to the nine STAT sites on the promoter of ATM, 53BP1, MDC1 DNA damage genes. As a consequence of this binding, there are less pSTAT3, more transcriptionally repressive histones (H3K27) and less transcriptionally active histones (H3K4, P300, Acy 300) binding to the promoters.…”
Section: Discussionmentioning
confidence: 81%
“…Laurence et al (2007) Con 1h provided evidence that IL-2 and STAT5a/b were the key regulators of Treg and served to constrain Th17 polarization. Yang et al (2011) reported that the induction of STAT5 binding by IL-2 was beneficial to STAT3 suppression. Thus, this study suggests that the activation of IL-6/STAT3 pathway might be involved in the progression of β-lg allergy.…”
Section: Discussionmentioning
confidence: 99%
“…2B). As STAT3 binds to the IL-17a promoter to initiate its transcription, and also competes with STAT5 binding which interferes with IL-17 transcription, 14,15 we evaluated the binding of both STAT proteins using chromatin immunoprecipitation (ChIP) assays followed by quantitative PCR (qPCR). STAT3 binding to the IL-17 promoter was diminished, whereas STAT5 binding was elevated in cells that lacked CTLA-4 engagement.…”
Section: Stat3 Activity Is Enhanced By Ctla-4 In Tc17 Cellsmentioning
confidence: 99%
“…In the nucleus, STAT3 and STAT5 compete for binding to the IL-17 promoter, leading to gene activation or silencing, respectively. 14,15 As STAT1 and STAT3 inhibit each other, relatively higher expression of STAT3 than STAT1 is required for the optimal activation of the transcriptional machinery for Tc17-related genes. 16,17 Tc17 cells have been shown to be tumor-promoting cells, but they can also contribute to tumor rejection.…”
Section: Introductionmentioning
confidence: 99%